PRIORITIES FOR IMPROVING THE MANAGEMENT OF THE PROCESS OF INFORMATION COOPERATION OF ORGANIZATIONS IN THE CONTEXT OF DIGITAL TRANSFORMATION (American Journal of Interdisciplinary Research and Development, 2024)
This article explores the crucial priorities for optimizing the management of information cooperation among organizations amidst the ongoing digital transformation. Through a comprehensive literature analysis, the study identifies key challenges and opportunities in information sharing and collaboration. The methods section delineates effective strategies for improving information cooperation management, followed by the results section showcasing the potential outcomes of implementing these strategies. The discussion delves into the implications of the findings, offering insights into fostering better collaboration in the digital age. Finally, conclusions and suggestions highlight actionable recommendations for organizations aiming to excel in information cooperation amidst digital transformation.